2023
DOI: 10.1039/d3ra07567b
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency energy transfer in the strong orange-red-emitting phosphor CeO2:Sm3+, Eu3+

Nguyen Van Hai,
Nguyen Thi Khanh Linh,
Dinh Thi Hien
et al.

Abstract: High-efficiency energy transfer (ET) from Sm3+ to Eu3+ leads to dominant red emission in Sm3+, Eu3+ co-doped single-phase cubic CeO2 phosphors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It is known that the CeO 2 host can efficiently absorb UV light and transfer its energy to RE (Eu) ions, making it an attractive UV-excited host. [10,20] Therefore, the emission efficiency of Eu-doped CeO 2 oxides could significantly enhance which are caused by those energy transfer (ET) and spectral resonance between the CTB and the 4 f-4 f transitions (Eu). [20,21] G. Vimal et al [22] reported the ET from the CeO 2 host to Eu 3 + in CeO 2 : Eu 3 + phosphor, resulting in its efficiency emission being enhanced.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that the CeO 2 host can efficiently absorb UV light and transfer its energy to RE (Eu) ions, making it an attractive UV-excited host. [10,20] Therefore, the emission efficiency of Eu-doped CeO 2 oxides could significantly enhance which are caused by those energy transfer (ET) and spectral resonance between the CTB and the 4 f-4 f transitions (Eu). [20,21] G. Vimal et al [22] reported the ET from the CeO 2 host to Eu 3 + in CeO 2 : Eu 3 + phosphor, resulting in its efficiency emission being enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Practically, rare-earth (RE) trivalent ions doped CeO 2 lattice is the simplest way to improve their physicochemical properties for industrial multifunction applications due to their close ionic radius to that of Ce 4 + ion. [9,10] Therefore, various appoaches to synthesizing REdoped CeO 2 nanoparticles include the hydrothermal method, [11] co-precipitation, [12] sol-gel, [13] solution combustion, [10,14] solidstate reaction, [15] etc. Notably, the combustion method was widely selected because of various advantages compared with other methods such as easy synthesis, energy saving, high purity, and good crystallinity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations